2010
DOI: 10.1673/031.010.6701
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillars and Host Plant Records for 59 Species of Geometridae (Lepidoptera) from a Montane Rainforest in Southern Ecuador

Abstract: During four months of field surveys at the Reserva Biológica San Francisco in the south Ecuadorian Andes, caterpillars of 59 Geometridae species were collected in a montane rainforest between 1800 and 2800m altitude and reared to adults. The resulting data on host plant affiliations of these species was collated. The preimaginal stages of 58 and adult stages of all 59 species are depicted in colour plates. Observations on morphology and behaviour are briefly described. Five species, documented for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
0
42
0
2
Order By: Relevance
“…The Central American geometrid fauna is poorly known with recent data from Costa Rica (Pitkin et al 1996;Brehm & Axmacher 2006, amongst others) and Nicaragua (Viidalepp, et al 2010). As there is a gap of 37 years between the El Salvadorean and Chilean findings it would suggest that they are unrelated in origin, especially if one considers that an 'intermediate' country such as Ecuador is well studied in terms of its geometrid fauna Bodner et al 2009;Strutzenberger et al 2010, amongst others) (the observation that the subfamily Sterrhinae is not well-represented at high altitudes, in fact, used data from an Ecuadorian study ). It needs to be considered if the 1998 specimen from Valparaíso (see above) was of Chinese ori- With the finding of four specimens of Rhodometra sacraria from Chile the genus Rhodometra Meyrick, 1892 now has three species in the Neotropical Region, in addition, to being the f irst taxon documented for Chile in the Rhodometrini.…”
Section: Resultsmentioning
confidence: 99%
“…The Central American geometrid fauna is poorly known with recent data from Costa Rica (Pitkin et al 1996;Brehm & Axmacher 2006, amongst others) and Nicaragua (Viidalepp, et al 2010). As there is a gap of 37 years between the El Salvadorean and Chilean findings it would suggest that they are unrelated in origin, especially if one considers that an 'intermediate' country such as Ecuador is well studied in terms of its geometrid fauna Bodner et al 2009;Strutzenberger et al 2010, amongst others) (the observation that the subfamily Sterrhinae is not well-represented at high altitudes, in fact, used data from an Ecuadorian study ). It needs to be considered if the 1998 specimen from Valparaíso (see above) was of Chinese ori- With the finding of four specimens of Rhodometra sacraria from Chile the genus Rhodometra Meyrick, 1892 now has three species in the Neotropical Region, in addition, to being the f irst taxon documented for Chile in the Rhodometrini.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the degree of host specificity for every caterpillar species, we combined data from this study, own unpublished observations, and host plant affiliation data from Brehm (2003), Bodner et al (2010a), Dyer et al (2010), and Robinson et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified the region as a global hotspot of geometrid diversity (Brehm et al 2005). For a still small, but ever growing fraction of moths also their functional relationships towards host plants become elucidated (Brehm 2003, Bodner et al 2010a. Against this background this paper aims at testing the following hypotheses:…”
mentioning
confidence: 99%
“…However, the biology of the Neotropical species is little known, with only a few host plant records published (Passoa 1983;Vargas 2007;Marconato et al 2008;Bodner et al 2010;Robinson et al 2010). In contrast, host plant relationships are better documented for the Nearctic species, many of which are polyphagous (Robinson et al 2010).…”
mentioning
confidence: 99%
“…Furthermore, this is also the first record of Anacardiaceae as host plant for a Neotropical species of Iridopsis. Previously known records for Neotropical Iridopsis included Asteraceae, Erithroxylaceae, Fabaceae and Viburnaceae (Passoa 1983;Vargas 2007;Marconato et al 2008;Bodner et al 2010;Robinson et al 2010).…”
mentioning
confidence: 99%